Relationships between morphological facies and the evolutionary processes of petroplinthites in the Southern Espinhaço Range (SE-Brazil) - de Campos, Daniela Schievano; Camêlo, Danilo de Lima; Silva, Alexandre Christófaro; dos Santos, Marcilene [UNESP]; Vidal-Torrado, Pablo (Elsevier, 2024)
Morphological facies of petroplinthites describe how soil components such as the soil matrix, nodules, pores, and coatings relate to each other in space. French scientists have extensively used such descriptions to interpret evolutionary processes and stages of petroplinthites (laterites, ferruginous duricrusts, ironstones) in Central and Western Africa. However, there has been little progress using the interpretation of petroplinthite facies in other parts of the world. This study explores the protocol in Brazilian petroplinthites with the aim of defining processes and identifying evolutionary stages based on analysis of the morphological differences in the petroplinthites from a pedogenetic perspective. The studies were concentrated in the Southern Espinhaço Range, southeast Brazil, and covered Petric or Pisoplinthic Plinthosol (Petroferric Oxisols) profiles with a wide morphological variety of petroplinthites. Based on a literature review, the aim was to standardize concepts and define the different morphological facies, before applying them to the petroplinthites of the study area. Geochemical and mineralogical analyses were added to the description of the facies to interpret the main pedogenetic processes and evolutionary sequences among the profiles. As such, macro and micro morphological descriptions were carried out in association with geochemical maps using SEM-EDS, and specific mineralogical characterization was performed using an electronic microprobe to characterize the main morphological facies. XRD, XRF, and magnetic susceptibility analyses were used to interpret the main formation, transformation, and degradation processes of the petroplinthites. The integration of these analyses enabled the association of the morphological facies with the petroplinthite evolutionary processes. Thus, while lamellar facies are shown to be directly associated with saprolitization processes, nodular and massive facies generally represent intense lateritization. Protopisolithic facies are commonly associated with transformation processes, with goethite precipitation and re-cementation of the matrix, while pisolithic facies are formed through degradation processes with intense mineral dissolution. Recovering the protocol for associating macro and micro morphological facies with geochemistry and mineralogy enabled improved interpretation of the genesis of petroplinthites, with clearer and more objective identification of the evolutionary stages, as well as their relationship with the landscape and the hydrological systems and environmental conditions.
Keywords: Ferricretes; Ferruginous duricrusts; Micromorphology; Petric Plinthosol; Petroferric Oxisols; Pisoplinthic Plinthosol